DEPRESSION IN SCHOOL TEACHERS DURING THE PANDEMIC PERIOD: INTEGRATIVE LITERATURE REVIEW - Jacob, Marcelo (Health and Society, 2023)
During the first wave of the COVID-19 pandemic in 2020, strict lockdown measures imposed, among others, a remote teaching format in many countries, causing an unprecedented shift in school-related activities. As a result, all classes had to switch quickly and unpredictably from a face-to-face teaching format to a remote one, contributing to creating a turbulent work environment for teachers. In Brazil, reports of anxiety, depression, and other problems related to the mental health of teachers are increasingly frequent, especially with the return of face-to-face classes, after two years of the pandemic, and the consequent return to the problems in the teaching structure present in the country since well before the public health crisis. However, the extent of the changes caused in the health and work conditions of basic education teachers in the pandemic period is still unclear, an issue that motivated the investigation and analysis of the main aspects of depression in school teachers in the pandemic period. For this, this review integrates results of studies on the impact of the Covid-19 pandemic on mental health, with the selection of 7 studies, whose results indicate that depression in school teachers can be influenced by several factors, such as anxiety and stress. generated by pressure for results, occupational stress, Internet Addiction Disorder and Burnout. In addition, the gender issue can also be a risk factor for depression in teachers, as women are more susceptible to developing the disorder.